How Do School Nurse Programs Influence Premarital Sexual behavior In Adolescents? (Indian Journal of Public Health Research & Development, 2020)
Background: Teens are very vulnerable to premarital sexual behavior. The impact includes unwantedteen pregnancy and sexually transmitted infections. Prevention efforts need to be done effectively and oneimportant way is through school nurse programs.Objective: This study aimed to identify the effects of school nurse programs on prevention premaritalsexual behavior.Method: This research was a quantitative, quasi-experimental study with a nonequivalent (pretest andposttest) control group design. This research was conducted in two schools from January to February 2017.Schools were determined based on preliminary studies with predetermined criteria. Determination of SchoolA as the intervention group and School B for the control group used a simple random sampling method. Thepurposive sampling method was used to select 68 students for the intervention group and 66 students forthe control group. The data were analyzed by paired t-tests. Ethical approval was given with permit numberRef: KE/FK950/EC/2015.Results: After the school nurse program, the values of healthy dating behavior, behavior of saying noto premarital sex and behavioral decision-making ability in the intervention group were higher than inthe control group: 0.200±0.42 vs. -0.203±0.20, p = 0.000; 0.193±0.40 vs. 0.032±0.43, p = 0.029; and0.032±0.18 vs. -0.251±0.23, p = 0.000 which were significantly difference (p < 0.05). Meanwhile, there wasalso an increase in the value of self-efficacy in adolescents in both the intervention and the control groups:0.017±0.22 vs. 0.053±0.19, p = 0.315, but the differences in the two groups were not significant.Conclusion: School nurse programs can effectively reduce premarital sexual behavior, especially byincreasing healthy dating behaviors, the behavior of saying no to premarital sex and behavioral decisionmakingabilities in adolescents.
Keywords: Adolescents, premarital sexual behavior, school nurse program, self-efficacy, dating behavior